Comparison of Postoperative Complications After Gastrectomy for Gastric Cancer with Antecolic Versus Retrocolic Reconstruction : A Population-Based Study - Junttila Anna; Helminen Olli; Helmiö Mika; Huhta Heikki; Jalkanen Aapo; Kallio Raija; Koivukangas Vesa; Kokkola Art; Laine Simo; Lietzen Elina; Louhimo Johanna; Meriläinen Sanna; et al. (Springer Nature, 2025)
Background: The purpose of this study was to examine the rates of 90-day anastomotic complications and other postoperative complications after total or partial gastrectomy with antecolic versus retrocolic reconstruction in a population-based setting.
Methods: This population-based nationwide retrospective cohort study included all patients undergoing total or partial gastrectomy for gastric adenocarcinoma in Finland in 2005-2016, with follow-up until 31 December 2019. Logistic regression provided odds ratios (ORs) with 95% confidence intervals (CIs) of 90-day mortality. Results were adjusted for age, sex, year of the surgery, comorbidities, tumor locations, pathological stage, and neoadjuvant therapy.
Results: A total of 2063 patients having gastrectomy with antecolic (n = 814) or retrocolic (n = 1249) reconstruction were identified from the registries. The anastomotic complication rate was 3.8% with antecolic reconstruction and 5.0% with retrocolic reconstruction. Antecolic reconstruction was not associated with a higher risk of anastomotic complications compared with retrocolic reconstruction in the adjusted analysis (OR 0.69, 95% CI 0.44-1.09) of the whole cohort or in the predefined subgroups. The reoperation rate was 8.2% with antecolic reconstruction and 7.7% with retrocolic reconstruction, without statistical significance. In subgroup analysis of total gastrectomy patients, the risk of major complications was lower with antecolic reconstruction compared with retrocolic reconstruction (OR 0.62, 95% CI 0.45-0.86).
Conclusions: The rate of anastomotic complications did not differ after antecolic versus retrocolic reconstruction after total or partial gastrectomy. In total gastrectomies, the risk of major complications was lower after antecolic compared with retrocolic reconstruction.